Associations of neck muscle strength and cervical spine mobility with future neck pain and disability: a prospective 16-year study - Multanen, Juhani; Häkkinen, Arja; Kautiainen, Hannu; Ylinen, Jari (BMC musculoskeletal disorders, 2021)
Background Neck pain has been associated with weaker neck muscle strength and decreased cervical spine range of motion. However, whether neck muscle strength or cervical spine mobility predict later neck disability has not been demonstrated. In this 16-year prospective study, we investigated whether neck muscle strength and cervical spine mobility are associated with future neck pain and related disability in women pain-free at baseline. Methods Maximal isometric neck muscle strength and passive range of motion (PROM) of the cervical spine of 220 women (mean age 40, standard deviation (SD) 12 years) were measured at baseline between 2000 and 2002. We conducted a postal survey 16 years later to determine whether any subjects had experienced neck pain and related disability. Linear regression analysis adjusted for age and body mass index was used to determine to what extent baseline neck strength and PROM values were associated with future neck pain and related disability assessed using the Neck Disability Index (NDI). Results The regression analysis Beta coefficient remained below 0.1 for all the neck strength and PROM values, indicating no association between neck pain and related disability. Of the 149 (68%) responders, mean NDI was lowest (3.3, SD 3.8) in participants who had experienced no neck pain ( n = 50), second lowest (7.7, SD 7.1) in those who had experienced occasional neck pain ( n = 94), and highest (19.6, SD 22.0) in those who had experienced chronic neck pain ( n = 5). Conclusions This 16-year prospective study found no evidence for an association between either neck muscle strength or mobility and the occurrence in later life of neck pain and disability. Therefore, screening healthy subjects for weaker neck muscle strength or poorer cervical spine mobility cannot be recommended for preventive purposes.